Pengaruh pertumbuhan ekonomi, indeks pembangunan manusia dan kepadatan penduduk terhadap tingkat kemiskinan kabupaten/kota di Provinsi Jambi - Rahma Wardana Putri; Junaidi Junaidi; Candra Mustika (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This study deals with the effect of economic growth, Human Development Index (HDI) and population density on the poverty levels of districts/cities in Jambi Province in 2013-2017. The type of data used in this study are combined secondary data from time series data and cross section data from 2013-2017. The data used is obtained from the official website of the Central Statistic Agency of Jambi Province. The analytical method used is panel data regression analysis. The result showed that the variabels of economic growth and population density had a siginificant effect on the poverty level of districts/cities in Jambi Province in 2013-2017. The coefficient of determination is 0.982702, which means that the independent variabels of economic growth, Human Developmet Index (HDI) and population density affect 98.27% of the dependent variabels of poverty in districts/cities in Jambi Province. Simultaneous test results (F test), show taht economic growth, Human Development Index (HDI) and population density simultaneously have a significant effect on the poverty level of districts/cities in Jambi Province. Keywords: Economic Growth, Human Development Index (HDI), Population Density, Poverty Level.